Influência das condições de síntese do LiSrPO4 dopado com íons lantanídeos trivalentes nas propriedades ópticas - Nascimento, Patresio Alexandro Miranda do (2017)
This study reports the synthesis, structural and optics characterization of LiSrPO4 pure and doped with Lanthanide ions as Ce3+, Eu3+ or Tb3+. The samples were synthesized via the Sol-gel route. Glucose was chosen as the chelating agent, however, samples were also produced without the use of the chelating agent, with the aim of studying its in uence on the structural and optical properties. Di erent temperatures of syntheses were used in the production of the samples. Samples were produced with stoichiometric variation of Li+ (excess and de ciency) and doped with Ce3+, Eu3+ or Tb3+. The temperature of 1000 C for 2 hours was found as the best condition to obtain the crystalline phase of pure and doped LiSrPO4 . The structural characterization of the samples was performed using X-ray di ractometry and from them it was possible to estimate the mean crystallite size of the samples. The use of glucose allows obtaining crystals of the order of 18 nm, presenting smaller sizes when compared to the route without using the glucose employing the calcination temperature of 1000 C for 2 hours. It was found that the change in temperature of calcination changes the average size of the crystallite in samples pure and doped. Samples produced with stoichiometric variation of Lithium doped have a mean crystallite size higher than pure samples, presenting an average size of 46 nm, 24 nm and 21 nm for samples doped with Ce3+, Eu3+ or Tb3+, respectively. The samples doped with Ce3+ exhibit excitation and emission bands in the UV and near-UV region, respectively. The increase of the Lithium concentration reduces the emission intensity of the samples doped with Ce3+. The samples doped with Eu3+ contains a band of transfer charge (260 nm) with an intensity equivalent to transition 7F0 ! 5L6 (394 nm), both of which were the most intense of the spectrum of excitation. The intensity of the emission of these samples increases with the increase of Li+ concentration, agreeing with the variation of the symmetric factor, in which it is veri ed that the Eu3+ ion is in a site of low symmetry. The high intensity of transitions 5D0 ! 7F2 and 5D0 ! 7F4 provides an emission in the red of the visible spectrum. The samples doped with Tb3+ contain a very intense excitation band in the UV region (219 nm). This high excitation intensity xviii xix results in very intense emission spectra. The increase in the concentration of Li+ reduces the emission intensity of the samples doped with Tb3+. The two peaks with maximum emission refer to transitions 5D3 ! 7F6 (380 nm) and 5D4 ! 7F5 (545 nm), resulting in an emission in the cyan region of the visible spectrum.